STUDI FENOMENOLOGI PERSONAL BRANDING PENDAKI GEN-Z DI MEDIA SOSIAL - Adani, Naufal Sallahudin; Setianingrum, Vinda Maya (Universitas Negeri Surabaya, 2024)
This research highlights the importance of personal branding, which is the process of creating a self-image to increase an individual's selling value. In the digital era, social media such as Instagram has become a primary tool in forming personal branding. Generation Z, who are active in mountain climbing, utilizes this platform to share experiences and build self-identity. This trend reflects how the hobby of climbing is used as a means of self-expression and social interaction. Using Montoya's personal branding theory, this study found that the aspects of